Sexual and age-related features of some parameters in healthy control and patients with arterial hypertension, ischemic heart disease, and their comorbidity - Pavlega, Hanna; Gozhenko, Anatoliy; Zukow, Walery (Journal of Education, Health and Sport, 2025)
Background: Cardiovascular diseases (CVD) exhibit well-documented sex-specific differences in epidemiology and clinical presentation. However, the interaction between sex and age in determining cardiovascular risk biomarkers remains incompletely understood, particularly across different age groups corresponding to reproductive status in women. Aim: To investigate sex- and age-related differences in cardiovascular, metabolic, and endothelial parameters in healthy controls and patients with arterial hypertension (AH), ischemic heart disease (IHD), and their comorbidity. Methods: This cross-sectional study included 172 participants: 151 patients (35 with IHD, 28 with AH, 58 with IHD&AH comorbidity, 20 with alcoholism&AH, 10 with obesity&AH) and 21 healthy controls. Participants were stratified by sex and age groups: young (<45 years), middle-aged (45-55 years), and older (>55 years). All biomarkers were standardized to sex-specific Z-scores to enable direct comparison across parameters and account for sex differences in reference ranges. We measured circulating endothelial cells (CECs), lipid profiles, metabolic parameters, and calculated atherogenicity indices. Forward stepwise discriminant analysis was performed to identify key distinguishing variables. Results: Discriminant analysis revealed 12 variables that significantly differentiated the six sex-age groups (Wilks’ λ=0.101, p<0.001). Age-related differences were most prominent along the first discriminant root (84.8% of variance), with elderly patients showing elevated cholesterol (Z-scores: 1.13±0.27 vs 0.09±0.25), triglycerides (0.76±0.37 vs -0.14±0.11), and initially altered CECs (0.91±0.17 vs -0.42±0.18), but reduced ankle-brachial index (-0.92±0.15 vs -0.67±0.15). Sex differences were most pronounced in young patients along the second root (7.0% of variance), with women showing higher BMI (Z: 1.83±0.62 vs -0.53±0.25) but paradoxically lower Klimov’s atherogenicity index (-0.97±0.64 vs -0.35±0.56). Notably, creatinine Z-scores revealed greater pathophysiological deviation in middle-aged women (2.45±0.37) versus men (1.27±0.25, p=0.012) despite similar raw values (109±3.7 vs 111±2.6 µM/L). Classification accuracy reached 70.3%, exceeding random distribution by 4.2-fold. Conclusions: Our findings demonstrate distinct age- and sex-specific patterns in cardiovascular risk markers, with sexual dimorphism being most pronounced in younger age groups and diminishing with age. Sex-specific Z-score standardization reveals pathophysiological deviations masked by raw values, particularly for parameters with sex-different reference ranges. These results suggest the need for age- and sex-specific approaches to cardiovascular risk assessment and management.